Updated checklist of the Canary Islands wild bees (Hymenoptera: Apoidea: Anthophila) with insights into their biogeographic patterns and citizen science - Lugo, David; Suárez, Daniel; Peña, Gustavo; Roche, Francisco La; Rúa, Pilar De La; Ruiz, Carlos (Zootaxa, 2026)
The wild bee fauna (Hymenoptera: Apoidea: Anthophila) of the Canary Islands has received considerable attention from researchers and naturalists over the years. However, since the last comprehensive report published in the 1990´s, critical knowledge gaps regarding taxonomy, distribution and origins remain. Here, we present an updated checklist of the bee species of the Canary Islands, incorporating recent taxonomic revisions, newly described species, and relevant distribution data by combining information from both literature and citizen science contributions. More than 8000 records from citizen science platforms, along with additional collections records, have been examined to update the spatial distribution coverage and address several biological knowledge gaps. Our results suggest a composition ruled by a high proportion of endemic and threatened species compared to adjacent continent areas. The present checklist encompasses 146 species and 46 subspecies for the archipelago, 60 of which are endemic species and 42 endemic subspecies. In total 63 new local records are provided and three species Lasioglossum medinai (Vachal, 1895), Seladonia gemmea (Dours, 1872) and Sphecodes rubripes Spinola, 1838 are reported for the first time. Our biogeographical approach reveals differences in faunistic composition among islands, identifying three clusters corresponding to species predominantly associated with eastern, central, and western islands. Overall, Canarian endemic and Palaearctic elements are consistently represented across the archipelago, with endemics notably dominant in the western islands and introduced global species more frequent in the central islands. In contrast, Saharo-Arabian and Mediterranean elements are more prominent in the eastern islands, likely reflecting their geographical proximity to North Africa.